2018
DOI: 10.3233/jad-180109
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Stimulation and Individualized Music Sessions on Older Adults with Severe Dementia: Effects on Mood, Behavior, and Biomedical Parameters

Abstract: Both interventions seem to be effective at managing mood and behavioral disturbances in the short term and at improving physiological rates, highlighting the efficacy of nonpharmacological treatments in patients with severe dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
71
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 62 publications
(81 reference statements)
3
71
1
5
Order By: Relevance
“…Further data extraction of 141 full‐text articles excluded 135 papers based on the inclusion criteria. Although six papers met the inclusion criteria, three papers were from the same research project as confirmed by the study author . Thus, a total of four studies were included in this review as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Further data extraction of 141 full‐text articles excluded 135 papers based on the inclusion criteria. Although six papers met the inclusion criteria, three papers were from the same research project as confirmed by the study author . Thus, a total of four studies were included in this review as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Severity of cognitive impairment was from mild to very severe. The number of participants ranged from 21 to 120 . Only one study specified the type of dementia (Alzheimer's disease) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations